Predicting Emirati student academic outcomes: school tracks and standardized tests - Al-Ali, Fatima; Rice, John (International Journal of Evaluation and Research in Education (IJERE), 2025)
Global education systems apply grouping strategies to enhance academic outcomes. The United Arab Emirates (UAE) has developed school tracks to address performance gaps by offering more varied high-school tracks while also creating a local Emirates Standardized Tests (EmSAT) for measurement. This study examines the impact of educational tracks in Emirati schools and EmSAT scores on UAE university students’ academic performance. A quantitative multivariate analysis of 3,190 University of Sharjah students compared the outcomes across different high school tracks and analyzed the predictive power of EmSAT scores on university cumulative grade point average (CGPA). EmSAT scores vary significantly by tracks, with elite students performing best, followed by those in the advanced and scientific tracks. Arabic and mathematics EmSAT scores predict CGPA more strongly than English, which has a moderate effect. General track students achieve higher CGPAs compared to other tracks, even after controlling EmSAT performance and gender, suggesting a complex relationship between high school experiences and university success. The findings highlight the track model’s effectiveness, with the elite fostering strong academic pathways. However, the overlap in university achievement between the general and advanced warrants further research. The study provides insights for policymakers to refine educational strategies and enhance student outcomes.